Método de avaliação do gerenciamento de resíduos em canteiro de obras da construção civil : proposta baseada em empresas construtoras da cidade de Natal-RN - Tavares, Dyanna Karla Pinheiro (2009)
According to great concern between the developed industrial activities and resultant impacts over the environment, an association of several factors have occurred, procedures to the efficient management of the rotation between economical development and the environment have been improved. A research in field have been realized inside building sites of companies in order to provide knowledge about the implemented and accomplish actions according to the resolution from CONAMA nº307. Trough the interview among the representations of the companies and photographic survey in loco, such as, what makes the companies implement this management, reutilization and recycling, transport and disposition. The present study had as objective: analyze the insertion of the used tools to residuals management, proposing improvements, in a way that it can be easily identified during the procedures execution in the building sites of the building companies of the city of Natal/RN. To reach the goal, in the first place a revision of the pertinent literature was performed; there for, it can be seen the relation between residues management and environment sustainability, once it happens in a continued way it may prevent the waste and reduces the risk that the activities way bring to the employees, community and environment; once found the great difficult faced with regard to labors, material, equipment, project, planning, costumer s interference, furnisher. And still, it could be verified wich materials generate greater indexes of residues in the works and the main occurrences of waste and loss. However a greater transparency is needed coming from the high administration in the commitment with the continued actions, to make it so, there must be a cultural change inside the company. There for there will be a greater productivity and quality of the under taking such as costumer s satisfaction